2002
DOI: 10.1097/00001888-200212000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Gender Discrimination and Sexual Harassment in Medical Education

Abstract: This study suggests that mistreatment in the form of GD/SH is prevalent in undergraduate medical education, particularly within core clerkships. Interventions focused on particular specialties and training periods may be helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
85
3
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 4 publications
12
85
3
3
Order By: Relevance
“…3 Gender discrimination and/or sexual harassment were reported in all academic contexts by 69% of female and 33% of male graduating medical students in a 1997 survey of 14 US medical schools, with 63% of women and 30% of men describing these problem behaviors during their core clerkships. 4 In another survey of 1001 graduating students from 8 US medical schools, 21% of the female students and 2% of the male students reported that they had experienced some form of sexual harassment in medical school. 5 In a 1991 survey of second-year residents about their working and learning environment, 63% of female respondents reported having experienced at least 1 episode of sexual harassment or discrimination.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…3 Gender discrimination and/or sexual harassment were reported in all academic contexts by 69% of female and 33% of male graduating medical students in a 1997 survey of 14 US medical schools, with 63% of women and 30% of men describing these problem behaviors during their core clerkships. 4 In another survey of 1001 graduating students from 8 US medical schools, 21% of the female students and 2% of the male students reported that they had experienced some form of sexual harassment in medical school. 5 In a 1991 survey of second-year residents about their working and learning environment, 63% of female respondents reported having experienced at least 1 episode of sexual harassment or discrimination.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Published reports and surveys suggest that this is a common problem, both here and in other countries, with up to three quarters of women experiencing sexual harassment in the workplace [6][7][8][9][10][11][12][13]. Men are also harassed and bullied but less frequently [8,9].…”
Section: Introductionmentioning
confidence: 96%
“…Published reports and surveys suggest that this is a common problem, both here and in other countries, with up to three quarters of women experiencing sexual harassment in the workplace [6][7][8][9][10][11][12][13]. Men are also harassed and bullied but less frequently [8,9]. Within the medical hierarchy medical students are in a particularly vulnerable position, by virtue of being in the most junior position and in most circumstances not having the protection of being an employee [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residents and students can be more vulnerable to harassment and assault due to the inherent power differentials embedded within medical education [2,3]. A 14-school study published in 2002 found that 83 percent of female students had experienced sexual harassment and/or gender discrimination during medical school [4]. On the other hand, less than 15 percent of students reported experiencing some type of sexual harassment or discrimination on the 2017 Association of American Medical Colleges (AAMC) Graduation Questionnaire [5].…”
Section: Introductionmentioning
confidence: 99%